Developing energy-based loading protocols for seismic evaluation of steel moment frames' components. (November 2020) - Safaei, Shayan; Erfani, Saeed
Abstract: One of the main obstacles at the very first step of every experimental or numerical investigation is to select proper loading scenarios for evaluating the seismic performance of structural elements. For both qualifying the structural members and developing behavioral models as the primary input for nonlinear analysis of structures, there is a need for loading regimes that are able to simulate loading conditions similar to real earthquakes. This paper discusses the methodology used to develop a series of energy-based loading protocols for testing beam to column connections and columns of steel special moment frames. Several relationships controlling the configuration of loading protocols are proposed based on results obtained from multiple nonlinear time history analyses that have been conducted on a variety of structures. The histories of cycles obtained from these loading regimes are case-specific in order to dissipate a certain amount of energy from each structural component within a definite time based on its properties. In the case of column axial loading protocol, in addition to a force-control regime, a displacement-control one is also introduced to eliminate the instability issues arising when force-control loading scenarios are employed. After presenting the required steps to implement the proposed loading protocols, their accuracy is investigated by comparing them to the results of nonlinear time history analyses as well as some conventional and well-known loading protocols. Highlights: Energy-Based loading protocols for beam to column connections and columns of steel moment frames are developed. The amplitudes of the cycles vary with the system properties to dissipate a specific energy density. In addition to a force control axial loading regime, a displacement control one is also introduced for columns. By specifying the required time for imposing the loading cycles, strain-rate effects can be investigated.